Integrating trunk endurance, dynamic stability, and in-game performance analysis in youth elite basketball players - Gál-Pottyondy, A.; Pálya, Z.; Trzaskoma, L.; Kiss, R. M. (BMC Sports Science, Medicine and Rehabilitation, 2025)
Background Physical preparation in basketball is essential but often limited by training time and prior focus on tactical and technical skills. While postural stability is known to assist injury prevention and performance, its specific impact on game-related performance remains unclear. With the development of motion analysis systems, the numerical values of external and internal loads measured during matches have become measurable. This study aimed to examine the relationship between postural stability and game-related performance and introduce a method for visualizing key competencies.